Deformation characteristics and seepage mechanism of fractured rock mass under triaxial compression process - Jilu Zhang; Xiaohan Zhou; Xinrong Liu; Yang Kong; Bin Xu; Lojain Suliman (Soils and Foundations, 2025)
Understanding the gas seepage characteristics within fractured rock masses is of great significance for the prediction and prevention of hazardous gases in underground engineering. The formation is actually under a triaxial non-uniform stress state as a result of geological tectonic forces. Few studies on gas seepage take into account various stress situations. In this study, the flow characteristics of precast fractured rock masses were investigated through laboratory triaxial tests. The research results show that the volume strain of precast fracture changes from expansion to contraction with the decrease of the fracture angle under axial load. The fracture permeability decreases with the increase of axial strain before rock mass failure. After failure, the increase in permeability is not only related to the confining pressure and fracture angle but also has a significant correlation with the failure mode. Considering the triaxial non-uniform stress state, a coupled calculation model for seepage-stress-damage was established, and the calculation method was verified to effectively reflect the deformation and seepage characteristics of fractures. The lateral force on the fracture surface mainly causes the permeability of precast fractures to increase, and the increase extent of fracture permeability is negatively correlated with the fracture angle and elastic modulus.